2014
DOI: 10.1017/s0022029914000260
|View full text |Cite
|
Sign up to set email alerts
|

Milk metabolites as indicators of mammary gland functions and milk quality

Abstract: The assumption, that metabolites derived from the activity of the mammary gland epithelial cells reflect changes in milk secretion and its coagulation properties, was tested in dairy cows. The experiment included cows with uninfected udders and cows with one of the glands infected by different bacteria specie. Analysis were carried at the cow level (including all four glands), or at the gland level. High and significant correlations among the concentrations of lactose, glucose, glucose-6-posphate, milk related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
30
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 29 publications
6
30
1
1
Order By: Relevance
“…Studies reported that different bacteria may cause different types of physico-chemical damage to the milk (Leigh et al, 1997;Silanikove et al, 2014). By activation of the host's innate immune system, milk from udders infected with different types of bacteria but with similar somatic cell count (SCC) may present different milk composition alterations related to a bacteria specific mixture of leukocyte populations and leukocyte-associated proteases (Coulon et al, 2002;Merin et al 2008;Leitner et al, 2006;Silanikove et al, 2014). As a result, high SCC has been associated with prolonged rennet clotting times and a weak coagulum, which, in turn, lead to increased moisture content…”
Section: Introductionmentioning
confidence: 99%
“…Studies reported that different bacteria may cause different types of physico-chemical damage to the milk (Leigh et al, 1997;Silanikove et al, 2014). By activation of the host's innate immune system, milk from udders infected with different types of bacteria but with similar somatic cell count (SCC) may present different milk composition alterations related to a bacteria specific mixture of leukocyte populations and leukocyte-associated proteases (Coulon et al, 2002;Merin et al 2008;Leitner et al, 2006;Silanikove et al, 2014). As a result, high SCC has been associated with prolonged rennet clotting times and a weak coagulum, which, in turn, lead to increased moisture content…”
Section: Introductionmentioning
confidence: 99%
“…In fact, CNS has been associated with subclinical or moderate clinical mastitis and with high spontaneous cure rates [ 37 40 ]. Other studies argue that CNS are the main species responsible for mammary gland infection in ruminants, causing significant changes in milk metabolites that play an important role in the quality of dairy products [ 41 , 42 ]. Regardless of the effect of CNS in mammary infections, milk yield, and downstream milk quality, we acknowledge that improvement on the capability of correctly diagnosing Staphylococcus sp.…”
Section: Discussionmentioning
confidence: 99%
“…Some substances, usually present in dairy products, were studied with the purpose of testing their possible interfering effect on D‐lactate analysis. The levels of common metabolites (glucose, pyruvic acid, and, especially, L‐stereoisomer of lactic acid) in biological samples are an order higher compared with the concentration of D‐lactate (Ahmed et al, ; Shapiro & Silanikove, ; Silanikove, Merin, Shapiro, & Leitner, ). It was shown that the mentioned above analytes (as well as ethanol) had no interfering effect on the biosensor analysis of D‐lactate (see Figure S1).…”
Section: Resultsmentioning
confidence: 99%